I was on brilliant.org learning probability. There was a process explaining how the distribution of a Poisson Random Variable can be obtained from a Binomial Random Variable.

Consider the binomial distribution:

$$ \begin{equation}\begin{aligned} P(X=k) &={\binom n k} p^k (1-p)^{n-k}\\ &=\frac{n!}{k!(n-k)!} p^k (1-p)^{n-k} \end{aligned}\end{equation} $$
Substitute $m=np$ , or $p=\frac{m}{n}$ : $$ \begin{equation}\begin{aligned} P(X=k) &=\frac{n!}{k!(n-k)!} \left(\frac{m}{n}\right)^k \left(1-\frac{m}{n}\right)^{n-k}\\ &=\frac{n!}{k!(n-k)!} \frac{m^k}{n^k} \left(1-\frac{m}{n}\right)^{n}\left(1-\frac{m}{n}\right)^{-k} \end{aligned}\end{equation} $$
Slightly rearrange $$ \begin{equation}\begin{aligned} &=\frac{n!}{n^k(n-k)!} \left(1-\frac{m}{n}\right)^{-k}\frac{m^k}{k!}\left(1-\frac{m}{n}\right)^{n} \end{aligned}\end{equation} $$

Note that $$ \begin{equation}\begin{aligned} & \lim_{n\rightarrow \infty} \frac{n!}{n^{k}(n-k)! } =1,\quad\lim_{n\rightarrow \infty} \left(1-\frac{m}{n}\right)^{-k} =1,\quad \lim_{n\rightarrow \infty} \left(1-\frac{m}{n}\right)^{n} =e^{-m} \end{aligned}\end{equation} $$

Thus, we have the final result which is equal to the formula for the Poisson distribution.

$$ =\frac{m^k e^{-m}}{k!} $$

In all these steps, what I don't understand is the following limit: $$ \lim_{n\rightarrow \infty} \frac{n!}{n^{k}(n-k)! } =1 $$


It is rather obvious if you cancel the factorials:

$$\frac{n!}{n^{k}(n-k)! } =\frac{\overbrace{n(n-1)\cdots (n-k+1)}^{k\; factors}}{n^k}= 1\cdot \left(1-\frac{1}{n}\right)\cdots \left(1-\frac{k-1}{n}\right)\stackrel{n \to \infty}{\longrightarrow} 1$$

  • $\begingroup$ Thank you so much. I didn't know it was right there under my eyes. $\endgroup$ – billyandriam Apr 13 at 5:01
  • $\begingroup$ You are welcome. This "not seeing the obvious" just happens once in a while, I think, to all who do maths. So, it is good to have a math platform like this one. :-) $\endgroup$ – trancelocation Apr 13 at 5:03

$$a_n=\frac{n!}{n^{k}(n-k)! }\implies \log(a_n)=\log(n!)-k \log(n)-\log((n-k)!)$$

Use Stirling approximation and continue with Taylor series to get $$\log(a_n)=\frac{k(1-k)}{2 n}+O\left(\frac{1}{n^2}\right)$$ Continue with Taylor $$a_n=e^{\log(a_n)}=1+\frac{k(1-k)}{2 n}+O\left(\frac{1}{n^2}\right)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.